Produção de exopolissacarídeos (EPS) por bactérias láticas visando encapsulação de Lactobacillus acidophilus La-5 pelo processo de Spray drying - Paulo, Elinalva Maciel (2010)
The bacterial cells when they are in harsh environments for survival develops a protection system, consisting primarily of exopolysaccharides. This process was developed artificially by microencapsulation. The initial step in the microencapsulation is the selection of appropriate polymer. Exopolysaccharides produced by lactic acid bacteria do not appear in the literature as polymers used for the microencapsulation process. This study aimed to produce exopolysaccharides from lactic acid bacteria, aiming its use in the microencapsulation of L. acidophilus La-5 by the process of spray drying for preservation purposes. Lactic acid bacteria were isolated from foods from the region of the semi-arid region. Was performed, screening and selection of lactic acid bacteria producing EPS, The strain selected asthe largest producer of this biopolymer pseudomesenteroides Leuconostoc, with60.2 g / L of gross income in EPS. Two types of exopolysaccharides (EPS I and EPS II) were produced by this strain were both identified as dextran á (1-6). EPS I was used in the encapsulation of cells of L. acidophilus La-5 using the spray drying process, used three types of encapsulating materials: dextran, alginate and alginate + dextran mixture. The morphological and granulometric in the microcapsules showed the formation of heterogeneous particles in the three treatments with an average size of 8 mm in diameter. The percentages of survival of cells in dextran microspheres, alginate and alginate / dextran, stored at 4 ° C for 120 days were 69.7%, 77.2% and 56.3% respectively. The results showed that the dextran can serve as an alternative method of encapsulating polymer micro-organisms.